Arabinogalactan-proteins in spore-producing land plants. (15th April 2019) - Classen, Birgit; Baumann, Alexander; Utermoehlen, Jon
Highlights: Current knowledge on AGPs of mosses, clubmosses and ferns is summarized. Possible functions of AGPs in spore-producing land plants are discussed. Suggestions for future investigations are given. Abstract: Arabinogalactan-proteins (AGPs) are proteoglycans of the extracellular matrix of plants that were first isolated and described in the 1970s. Today, the consensus is that the following features are regarded as typical for these molecules: a large carbohydrate part of arabinogalactans (approximately around 90% of the molecule), that consists mainly of 3-, 6- and 3, 6-linked β-d -Gal p residues, substituted with α-l -Ara f residues a small protein moiety mostly rich in hydroxyproline the ability to precipitate with Yariv phenylglycosides, e.g. the β-glucosyl Yariv reagent In contrast to broad knowledge on AGPs in seed plants, insight in occurrence and structure of AGPs in spore-producing land plants (bryophytes, lycophytes and monilophytes) is very limited, although these plants are the closest living relatives to seed plants. In general, understanding of cell wall evolution is incomplete due to limited knowledge of cell wall structure of non-flowering plants. In this review, current knowledge on AGPs of mosses, clubmosses and ferns is summarized, possible functions are discussed and suggestions for future investigations are given.